Hierarchical structure for enhancing the innovation in the MSME sector of India. (2017) - Raghuvanshi, Juhi; Ghosh, P.K.; Agrawal, Rajat; Gupta, Himanshu
MSMEs are playing a very important role not only in providing employment to the millions of people, but also contributing in the overall economic development and social prosperity. To fulfil the goal of becoming an innovation driven economy, government is focusing on fostering innovation in the MSME sector. The lack of proper management and structure for identifying and enhancing the innovation in this sector results in few success stories. However, the literature supports the importance of various factors that enhance innovation, but pays less attention to how this process takes place in MSME sector. The aim of this study is to identify and rank the enablers of innovation in Indian MSMEs. This paper proposes a hierarchical structure which is based on ISM approach to prioritise the enablers of innovation in MSMEs. Lastly, MICMAC analysis has been conducted to examine the driving and the dependence power.